Analysis of Energy Efficiency of Rotate Flettner Rotor Based on Variation in Wind Direction and Rotor’s Material - Jürgen Siegl; Irfan Syarief Arief; Akbar Rizqi Hartawan (Institut Teknologi Sepuluh Nopember, 2020)
Flettner rotor is a cylindrical object which installed vertically on the ship's body. It rotates on its axis to utilize the airflow from the wind and help the ship to generate additional thrust force by using the principle of magnus effect. This additional thrust force produced by the flettner rotor helps to reduce the fuel consumption which used as an energy source for the main or auxiliary engine. However, the flettner rotor has possibilities to operate in a certain different condition which can affect the efficiency of the flettner rotor usage. The discussion is to find out how much power is needed to rotate a rotor based on the variation of the material being used, how does the wind direction affect the performance of the flettner rotor as an alternative ship propulsion system, how does the energy efficiency get affected by the variation of material and the wind direction. From the discussion of this bachelor thesis, it is concluded that aluminum is the material that requires the least power to rotate a flettner rotor with 77,2276 kW on the speed of 14.4 rad/s and it gives its maximum contribution when the wind direction towards the flettner rotor is coming through the port side of the ship with the angle of 90 ° and the flettner rotor rotates in clockwise direction. It is also concluded that the best configuration of flettner rotor to produce a good energy efficiency are by using aluminum as the rotor’s material, having wind that coming through from the angle of 90°, and the flettner rotor rotates at 14.4 rad/s with apparent wind speed at 7.2 m/s. This configuration can save fuel consumption of the ship up until 570.768 kg on 5000 km voyage.